Determination of Yield and Quality Performances of Silage Maize Cultivars to be Grown as Second Crop under Çukurova Conditions - Yasin Korkmaz; Tugay Ayasan; Sait Aykanat; Mustafa Avcı (Turkish Journal of Agriculture: Food Science and Technology)
The research was carried out in the Eastern Mediterranean Agricultural Research Institute-Hacı Ali location with 4 replications according to the randomized block trial design in 2013-2014. 13 public and 1 private sector maize variety were used as material in the trials. According to the results of the analysis, it was determined that the maize varieties examined showed statistically significant differences in plant properties, dry grass and silage quality. Average plant height, number of leaves, leaf ratio, stem diameter, number of cob, stem ratio, cob ratio and green grass yield were 249.9 cm, 12.97 plant/piece, 19.24%, 22.08 mm, 0.93 plant/unit, 38.40% and 4,251.57 kg/da respectively. According to the analysis, it was observed that the average crude protein content, ADF ratio, NDF ratio, crude ash content, digestible dry matter ratio, crude protein yield, dry matter rate, dry matter yield and hay yield were 8.80%, 34.91%, 59.7%, 7.2%, 61.7%, 993.9 kg/ha, 29.4%, 11,640 kg/ha 12,570 kg/ha in dry grass, respectively. For the silage of varieties, the average crude protein content, ADF ratio, NDF ratio, pH, digestible dry matter rate, dry matter ratio, crude protein yield and Fleig score were 8.22%, 29.27%, 50.48%, 3.57, 66.1%, 28.14%, 926 kg/ha and 118.35, respectively. Burak, Sasa 1 and Ada 334 genotypes performed better in terms of green yield per hectare (53,650, 50,290 and 45,630 kg/ha) and dry matter yield (14,710, 12,810 and 12,410 kg/ha). These varieties can be recommended to producers as silage maize varieties under second crop conditions in Çukurova region of Turkey.